Electrospun highly corrosion-resistant polystyrene–nickel oxide superhydrophobic nanocomposite coating - A. Bahgat Radwan (14151102) (2022)
A key challenge in producing superhydrophobic coatings (SHC) is to tailor the surface morphology on the micro-nanometer scale. In this work, a feasible and straightforward route was employed to manufacture polystyrene/nickel oxide (PSN) nanocomposite superhydrophobic coatings on aluminum alloys to mitigate their corrosion in a saline environment. Different techniques were employed to explore the influence of the addition of NiO nanoparticles to the as-prepared coatings. PSN-2 composite with ~ 4.3 wt% of NiO exhibited the highest water contact angle (WCA) of 155° ± 2 and contact angle hysteresis (CAH) of 5°. Graphic abstract EIS Nyquist plots of 3 g of electrospun polystyrene coatings (a) without and with (b) 0.1, (c) 0.15, and (d) 0.2 g of NiO. Other Information Published in: Journal of Applied Electrochemistry License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10800-021-01603-8